2017
DOI: 10.1038/s41467-017-00025-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic CRAC uncovers a role for Nab3 in determining gene expression profiles during stress

Abstract: RNA-binding proteins play a key role in shaping gene expression profiles during stress, however, little is known about the dynamic nature of these interactions and how this influences the kinetics of gene expression. To address this, we developed kinetic cross-linking and analysis of cDNAs (χCRAC), an ultraviolet cross-linking method that enabled us to quantitatively measure the dynamics of protein–RNA interactions in vivo on a minute time-scale. Here, using χCRAC we measure the global RNA-binding dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 61 publications
(83 reference statements)
0
65
0
Order By: Relevance
“…CRAC was performed exactly as recently described [41]. Cells were cross-linked in the Vari-X-linker for 12 seconds and CRAC libraries were paired-end sequenced (50 bp) on a HiSeq2500 at Edinburgh Genomics, University of Edinburgh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRAC was performed exactly as recently described [41]. Cells were cross-linked in the Vari-X-linker for 12 seconds and CRAC libraries were paired-end sequenced (50 bp) on a HiSeq2500 at Edinburgh Genomics, University of Edinburgh.…”
Section: Methodsmentioning
confidence: 99%
“…GSE87480). For CRAC data analysis, data from two biological replicates were analyzed as described[41]; yielding essentially the same outcomes; the data set with the better coverage (1,737,418 reads in data-set II vs 361,408 reads in data-set I) has been used for the presented figures. Hybrids of different RNAs crosslinked to Kre33 were identified in both data sets using the HYB-pipeline exactly as described [29].…”
Section: Methodsmentioning
confidence: 99%
“…Nrd1 mutants are synthetic lethal, with mutations that activate the Ras-protein kinase A (PKA) signaling pathway, and the pattern of Nrd1 binding changes upon glucose deprivation (42). Recent studies have shown that Nab3 is also important in reshaping the transcriptome in response to glucose deprivation (45,55). In this paper, we provide additional evidence that Nab3 is important in regulating genes that are required for uptake and catabolism of nonpreferred nitrogen sources, implicating the NNS complex in the regulation of genes in response to either carbon or nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
“…1216 More recently, the strong propensity of single-stranded CLPs to bind native collagen via a strand invasion process has been reported 17 and has permitted the utilization of CLPs as staining reagents to detect minute quantities of collagens in human tissues including skin, cornea, bone 18 and liver. 19 In vivo studies suggest that CLPs are able to permeate and accumulate in tissues with high levels of matrix metalloproteinase (MMP) activities and/or collagen damage, such as prostate tumor xenografts, tendon, 20 and articular cartilage. 21 Despite the great potential of using CLPs as a novel biomaterial for tracking pathological collagens, the utilization of these peptides as building blocks in generating nanoscale drug carriers is very limited.…”
Section: Introductionmentioning
confidence: 99%